Analisis Terrain Pada Lahan Berlereng Melalui Interpretasi Foto Udara Drone - Solihin, Muhammad Amir; Siswanto, Shantosa Yudha; Kencana, Dika (Soilrens, 2023)
Terrain analysis on land can be done through field activities or remote sensing. The development of aerial photography technology through drones can be used to identify land conditions, especially on narrow land, and requires large-scale maps. Terrain characterization can use a Digital Elevation Model (DEM) generated through aerial photography with drone vehicles. This study aimed to determine the research location's topographic characteristics, scale, and class of map geometry accuracy. The research location is in the Eastern Region of Padjadjaran Jatinangor University, Hegarmanah Village, Jatinangor District, part of the Cikeruh Sub Das. The method used is a descriptive survey method and quantitative data analysis. The results showed that the topographic characteristics of the study location had an elevation of 715 – 747 m above sea level and a flat slope class (0 – 3%) – steep (>60%), which was dominated by a steep slope class (26 – 40%) on 55 land units. The aerial photography used meets the standard of map accuracy class at a scale of 1:2,500 class 3